How much emergency department use by vulnerable populations is potentially preventable?: A period prevalence study of linked public hospital data in South Australia. Issue 1 (17th January 2019) - Banham, David; Karnon, Jonathan; Densley, Kirsten; Lynch, John W
Abstract : Objectives: To quantify emergency department (ED) presentations by individuals within vulnerable populations compared with other adults and the extent to which these are potentially preventable. Design: Period prevalence study from 2005-2006 to 2010–2011. Setting: Person-linked, ED administrative records for public hospitals in South Australia. Participants: Adults aged 20 or more in South Australia's metropolitan area presenting to ED and categorised as Refugee and Asylum Seeker Countries of birth (RASC); Aboriginal; those aged 75 years or more; or All others. Main outcome measures: Unadjusted rates of ambulatory care sensitive condition (ACSC), general practitioner (GP)–type presentations and associated direct ED costs among mutually exclusive groups of individuals. Results: Disparity between RASC and All others was greatest for GP-type presentations (423.7 and 240.1 persons per 1000 population, respectively) with excess costs of A106 573 (95% CI A98 775 to A114 371) per 1000 population. Aboriginal had highest acute ACSC presenter rates (125.8 against 51.6 per 1000 population) with twice the risk of multiple presentations and A108 701 (95% CI A374 to A123 029) per 1000 excess costs. Those aged 75 or more had highest chronic ACSC presenter rates (119.7vs21.1 per 1000), threefold risk of further presentations (incidence rate ratio 3.20, 95% CI 3.14 to 3.26) and excess cost of A385 (95% CI A178 160 to A184 609) per 1000 population. Conclusions: Vulnerable groups had excess ED presentations for a range of issues potentially better addressed through primary and community healthcare. The observed differences suggest inequities in the uptake of effective primary and community care and represent a source of excess cost to the public hospital system.